S84 The effect of patient ventilator asynchrony (PVA) on health related quality of life during initiation of home mechanical ventilation (HMV). (14th November 2013) - Ramsay, MC; Mandal, S; Suh, E-; Steier, J; Simonds, A; Hart, N
Abstract : Introduction: Poor patient-ventilator interaction has been shown to adversely affect respiratory muscle unloading, sleep quality, gas exchange and patient comfort whilst on ventilation. We hypothesised that nocturnal PVA during the first 3 months HMV initiation would have an adverse effect on patient health related quality of life. Methods: Recording neural respiratory drive, as assessed by the parasternal intercostal electromyogram, respiratory inductance plethysmography and mask pressure waveform we performed a comprehensive assessment of PVA overnight both on initiation of HMV and at 3 months. Asynchrony levels were recorded as a percentage of the total of number of breaths that were both requested and received by the patient overnight. The severe respiratory insufficiency questionnaire (SRI) was completed by patients at both of these hospital visits. Daytime arterial partial pressure of carbon dioxide (Pa CO2 ) was also assessed. Results: 16 patients (8 male) admitted for initiation of HMV were recruited. 7 with neuromuscular or chest wall disease, 6 with chronic obstructive pulmonary disease and 3 with obesity related respiratory failure. Adherence to ventilation at 3 months was 6h 38m (1h35m-7h32m). There was an overall improvement in SRI scores of 9.5 (-0.7 to 18.2) points with the largest improvement observed in the anxiety component with an increase of 20 (5.6–35) points followed by the sleep component of 12.5 (3.6–28.6) points over the 3 months. A significant inverse correlation was observed with the change in asynchrony levels and the change in SRI scores over the 3 month assessment period (rs = -0.70; p = 0.02; Figure 1 ). No significant correlation was observed between the change in Pa CO2 and change in SRI score. Conclusion: Enhancing patient-ventilator interaction, in particular reducing patient-ventilator asynchrony, had a direct correlation with improving health related quality of life of patients receiving HMV. Importantly, the anxiety and sleep components of the SRI were the most improved over the 3 months of treatment indicating the enhancement in perceived sleep quality with the psychological benefit of HMV treatment.